PHOTOTHERMAL THERAPY OF TRIPLE-NEGATIVE BREAST CANCER USING FOLIC ACID-TARGETED GOLD NANORODS - David Mayers; Jemima Reid; Shannon Thompson (Journal of Biomedical and Techno Nanomaterials, 2025)
Triple-negative breast cancer (TNBC) is an aggressive breast cancer subtype characterized by the absence of hormone receptors and HER2 expression, resulting in limited therapeutic options and poor clinical prognosis. Conventional treatments such as chemotherapy often lack selectivity and are associated with significant systemic toxicity, highlighting the urgent need for more precise and effective therapeutic strategies. This study aims to develop and evaluate folic acid–targeted gold nanorods as a photothermal therapy platform for selective treatment of TNBC. An experimental nanomedicine approach was employed, involving the synthesis of gold nanorods, surface functionalization with folic acid to enable folate receptor–mediated targeting, physicochemical characterization, and biological evaluation in TNBC models. Photothermal performance was assessed under near-infrared laser irradiation, while cellular uptake, cytotoxicity, and therapeutic selectivity were systematically analyzed. The results demonstrate that folic acid functionalization significantly enhanced nanoparticle uptake by TNBC cells, leading to higher localized temperature elevation and pronounced cancer cell ablation compared to non-targeted nanorods. Minimal cytotoxic effects were observed in normal breast cells, indicating favorable selectivity. In conclusion, folic acid–targeted gold nanorods provide an effective and selective photothermal therapy strategy for TNBC. This approach shows strong potential for advancing targeted nanomedicine and offers a promising alternative for treating aggressive breast cancer subtypes.